2017
DOI: 10.3390/agronomy7020042
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organic and Inorganic Fertilizers on the Yield of Two Contrasting Soybean Varieties and Residual Nutrient Effects on a Subsequent Finger Millet Crop

Abstract: The problems of low soil fertility resulting from continuous monocropping, crop residue removal and limited fertilizer use represent key challenges to produce surplus food for the ever increasing population of Ethiopia. However, the practices of crop rotation and integrated sources of fertilizer uses could potentially improve soil fertility and productivity. In 2012 and 2014, soybean with different trials consisting of two soybean varieties (Boshe and Ethio-ugozilavia), three levels of farm yard manure (FYM) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In economic terms, the literature (e.g., Abebe and Debebe, 2019;Kassie et al, 2009;Usman et al, 2015;Zerihun and Haile, 2017) provides ample evidence regarding the positive effects of organic fertilizer on crop productivity; hence farmer welfare. For instance, Gelgo et al (2016) reported increased incomes of farmers who adopted the input in the Shashemene District of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In economic terms, the literature (e.g., Abebe and Debebe, 2019;Kassie et al, 2009;Usman et al, 2015;Zerihun and Haile, 2017) provides ample evidence regarding the positive effects of organic fertilizer on crop productivity; hence farmer welfare. For instance, Gelgo et al (2016) reported increased incomes of farmers who adopted the input in the Shashemene District of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies could not identify the most suitable organic fertilizer for specific crops during each planting season (Dadi et al 2019;Madhumita and Ashalata 2019;Najla et al 2018). Zerihun and Haile (2017) tested the effect of organic and inorganic fertilizers on the yield of two soybean varieties and found out that the response of soybean varieties to applied fertilizers was significantly affected by rainfall and its geographical distribution at the two seasons. In another study, Mukhtar et al (2010) analyzed characters of sweet potato varieties grown at varying levels of organic and inorganic fertilizer during the wet seasons of 2004 and 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Application of 7.5 t cow manure or goat manure/ha is more efficient in producing organic soybeans compared to the dose of 10 or 15 t/ha (Sudarsono et al, 2013). However, according to Zerihun and Haile (2017), the application of 3 t manure/ha can save 70-85% of input costs for the purchase of inorganic fertilizer. Mamia et al (2018) recommend the use of 10 t chicken manure/ha + 75% recommendation of inorganic fertilizer or 2 t vermicompost/ha + 75% recommendation of inorganic fertilizer compared to 100% of inorganic fertilizer to obtain soybean yield of 2 t/ha because it is more environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%